Gambaran pengetahuan, sikap, dan tindakan dokter keluarga di Sulawesi Utara dalam menghadapi bencana - Elsatioria Sibarani; Iyone Esra Tiurma Siagian; Henry Malcom Frank Palandeng (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2022)
Background: Family physicians as primary care doctors and first medical contacts in providing services through a reciprocal referral mechanism including in disaster management and emergency services to prevent and reduce the impact caused by disasters. North Sulawesi as a disaster-prone area shows the high need for doctors who are responsive and ready to handle disasters which are influenced by factors of knowledge, attitudes, and actions in dealing with disasters. Purpose: To find out the knowledge, attitudes, and actions of family physicians in North Sulawesi in dealing with disasters. Methods: This research is descriptive in nature with a cross-sectional research design for all primary care family medicine specialists in North Sulawesi. This research used a purposive sampling method which was carried out in October-November 2022 and found 29 respondents who met the inclusion and exclusion criteria. Result: Family physicians in North Sulawesi have good knowledge, positive attitudes, and adequate actions in dealing with disasters. Keywords: family physicians, knowledge, attitude, action, disaster